[Budget impact analysis for peginterferon beta-1a in relapsing remitting multiple sclerosis in Italy] - Sergio Iannazzo (Farmeconomia: Health Economics and Therapeutic Pathways, 2016)
BACKGROUND: Peginterferon beta-1a, injected every two weeks, is the first approved pegylated interferon beta-1a for the treatment of relapsing remitting multiple sclerosis (RRMS). The objective of this analysis was to estimate the economic impact due to the introduction of peginterferon beta-1a in Italy. METHODS: This analysis was conducted with a three-year time horizon with the support of a simple decision-analytic model adopting the perspective of the Italian National Healthcare Service (NHS). Healthcare costs sustained by the Italian NHS to manage the RRMS population (drug treatment, monitoring, relapse management, adverse events management) were calculated over 3 years and compared in two scenarios: the base scenario where interferons-beta and glatiramer acetate (GA) are used to treat RRMS patients, and an alternative scenario where peginterferon beta-1a can also be used to treat RRMS patients. The target population was approximately 35,500, 37,500 and 39,500 patients at year 1, 2 and 3 respectively, based on the published literature and market data. The efficacy of treatments was simulated as a reduction of relapse rates and was derived from a Network Meta-analysis. Unit costs were based on current prices and tariffs, and the published literature. A one-way sensitivity analysis was developed. RESULTS: According to current price and described assumptions, it was estimated that the introduction of peginterferon beta-1a would result in a decrease of total costs when compared with the base scenario. The cost in the base scenario was estimated to be  € 321.5, € 339.7 and € 357.8 million in years 1, 2, and 3, respectively. In the alternative scenario, the same costs resulted in about € 321.1, € 338.6 and € 356.2 million, respectively. The cumulative budget impact over three years period was approximately a cost saving of € 3.1 million (about 0.3% saving). CONCLUSION: The adoption of peginterferon beta-1a for the treatment of RRMS would be viewed as economically sustainable by the Italian NHS.